Are individual and social factors specific to the home associated with children's behaviour and physical environment at home?. Issue 19 (2nd October 2021) - Sheldrick, Michael P. R.; Maitland, Clover; Mackintosh, Kelly A.; Rosenberg, Michael; Griffiths, Lucy J.; Fry, Richard; Stratton, Gareth
ABSTRACT: This study used linear regression analyses to investigate the influence of parent-reported home-specific social and individual factors on: (i) 235 children's home-based objectively measured overall sitting time, breaks in sitting, and PA, and; (ii) the home physical environment via an audit. Parental importance assigned to active play for children was positively associated with PA equipment (accessibility and availability), as well as light physical activity (LPA) and sitting breaks on both weekdays and weekend days. Parental preference for being active at home and limits on screen-time were associated with less household media equipment and portable media equipment, respectively. Greater parental importance placed on playing electronic games/using computers for fun was associated with less LPA and more sitting on weekdays. Further, children who preferred being sedentary sat more and engaged in less moderate-vigorous physical activity (MVPA) on weekdays. Parental and child preferences and priorities, as well as parental rules for activity at home, were associated with children's home-based sitting and PA, especially on weekdays. Such factors were also associated with the physical environment in the expected directions. The findings suggest interventions need to target social and individual factors, alongside adapting the physical environment to create homes more promotive of physical activity.